A negociação coletiva e a intangibilidade dos direitos humanos da personalidade do trabalhador assalariado - Machado, Fernanda Modolo Vieira (2006)
Beginning with a non eminent sociological approach of the collective barganing and the personell rights of the employee, although legal, this dissertation approaches and analyzes: the performance of the collective berganing ahead of the personality rights of the wage-earning worker, approaching in an demonstrative way, the right to the intimacy and to the privacy that the pregnant employee has in the face of employment relationship. The central objective of this work is to verify if the collective instruments of work, decurrent from the collective barganing, such as: collective convention and collective agreement can make use in valid and efficient way on human rights of the diligent wageearner ´s personality. The approaching method is hypothetical-deductive, when inquiring about if the legal institute of the collective barganing can efficaciously and efficiently make use on basic right of personality of the wage-earning worker, leading on the premise of that the collective barganing is one of the forms of implementation of the human rights of the workers. The research techniques are documentary; as primary source, and bibliographical, as secondary. One concludes, therefore, that the collective barganing cannot efficaciously and nor efficiently make use on rights of personality of the wageearning worker.